Democracy, Effective Referral, and the Instrumentalization of Patients - Platt, Elyse (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
Philosophers such as Roger Trigg have taken issue with the College of Physicians and Surgeons of Ontario policy on effective referral arguing that it is an example of a culture of consumerism in medicine. In this paper, I take issue with this position and instead argue that physicians who fail to effective refer are instead misusing their power as gatekeepers to healthcare.